Of Monsters and Men: A Spectrum View of the Imago Dei - C. A. McIntosh (Religions, 2023)
I explore the view that the imago Dei is essential to us as humans but accidental to us as persons. To image God is to resemble God, and resemblance comes in degrees. This has the straightforward—and perhaps disturbing—implication that we can be more or less human, and possibly cease to be human entirely. Hence, I call it the spectrum view. I argue that the spectrum view is complementary to the Biblical data, helps explain the empirical reality of horrendous evil, and offers an elegant rapprochement between the traditional view of hell and its rivals.